2020
DOI: 10.3390/jpm10030125
|View full text |Cite
|
Sign up to set email alerts
|

The Cytokinesis-Block Micronucleus Assay on Human Isolated Fresh and Cryopreserved Peripheral Blood Mononuclear Cells

Abstract: The cytokinesis-block micronucleus (CBMN) assay is a standardized method used for genotoxicity studies. Conventional whole blood cultures (WBC) are often used for this assay, although the assay can also be performed on isolated peripheral blood mononuclear cell (PBMC) cultures. However, the standardization of a protocol for the PBMC CBMN assay has not been investigated extensively. The aim of this study was to optimize a reliable CBMN assay protocol for fresh and cryopreserved peripheral blood mononuclear cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…The absence of such an effect is required when cryopreserved blood samples are used in radiosensitivity assessment. Our results are in agreement with the observations of Sioen et al and Zijno et al In both studies, the authors demonstrated that the length of the cryopreservation period had also no influence on MN yields in cryopreserved isolated PBMCs (Zijno et al 2007;Sioen et al 2020). Taken together, our first results with the MN assay suggest that the radiation response of lymphocytes, cryopreserved in whole blood samples, is similar to that observed in fresh whole blood samples.…”
Section: Mn Values As a Function Of Cryopreservation Time Were Analyzed By Linear Regressions Analysissupporting
confidence: 93%
See 4 more Smart Citations
“…The absence of such an effect is required when cryopreserved blood samples are used in radiosensitivity assessment. Our results are in agreement with the observations of Sioen et al and Zijno et al In both studies, the authors demonstrated that the length of the cryopreservation period had also no influence on MN yields in cryopreserved isolated PBMCs (Zijno et al 2007;Sioen et al 2020). Taken together, our first results with the MN assay suggest that the radiation response of lymphocytes, cryopreserved in whole blood samples, is similar to that observed in fresh whole blood samples.…”
Section: Mn Values As a Function Of Cryopreservation Time Were Analyzed By Linear Regressions Analysissupporting
confidence: 93%
“…An earlier study of our group showed that X-rays induced MN in frozen isolated PBMCs were significantly higher than in fresh isolated PBMCs. However, no difference seemed to be observed between MN yields of frozen isolated PBMCs and fresh whole blood cultures (Sioen et al 2020).…”
Section: Accepted Manuscript Discussionmentioning
confidence: 86%
See 3 more Smart Citations